1998
DOI: 10.1046/j.1365-2540.1998.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of an opportunistic parasitoid in an agricultural landscape

Abstract: Parasitoid insects that use different hosts can have a subdivided population structure that corresponds to host use. A subdivided population structure may favour local adaptation of subpopulations to small-scale environmental differences and may promote their genetic divergence. In this paper, heritable Random Amplified Polymorphic DNA (RAPD) markers visualized by single strand conformational polymorphisms (SSCP) analysis were used to examine the population structure of the parasitoid wasp Diaeretiella rapae (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…However, D. rapae females remained about 1.5-fold longer on M. persicae patch on oilseed rape leaf than A. matricariae females, and were therefore likely to be attacking more aphids. Although D. rapae have been reported on a variety of crops (Pike et al, 2000), it is clear from the literature that it is mainly found on cruciferous plants (Bahana & Karhioc, 1986;Ohiman & Kunar, 1986;Souza et al, 1992;Vaughn & Antolin, 1998;Bijaya Devi et al, 1999), and particularly on Brevicoryne brassicae (Mackauer & Kambhampati, 1984;Gabrys et al, 1998). When M. persicae is found on cruciferous crops, it is also reported as a potential host for D. rapae (Lyon, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…However, D. rapae females remained about 1.5-fold longer on M. persicae patch on oilseed rape leaf than A. matricariae females, and were therefore likely to be attacking more aphids. Although D. rapae have been reported on a variety of crops (Pike et al, 2000), it is clear from the literature that it is mainly found on cruciferous plants (Bahana & Karhioc, 1986;Ohiman & Kunar, 1986;Souza et al, 1992;Vaughn & Antolin, 1998;Bijaya Devi et al, 1999), and particularly on Brevicoryne brassicae (Mackauer & Kambhampati, 1984;Gabrys et al, 1998). When M. persicae is found on cruciferous crops, it is also reported as a potential host for D. rapae (Lyon, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parasitoids also have to choose a suitable developmental stage within each host species as instars provide another level of resource and defensive variability (Gerling et al 1990). When parasitoid species occur over a wide geographical range, divergent populations can form that are adapted to survive on the sympatric host species which are most prevalent in their region (Vaughn & Antolin 1996). Studies have demonstrated that the same species of parasitoid from different populations can vary in morphology (Biron et al 2002) and behaviour (Kraaijeveld et al 1995), which has been attributed to a combination of selective pressures on physiological and behavioural traits that, over time, result in local adaptation (Thompson 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This information could be crucial, because during this season the aphid parasitoid populations can be different from spring due to summer gap (when there is no canola or cruciferous in the fields) and the different environment around the new field of canola in autumn (the majority of other fields are empty). Two of the most frequently reported species on cruciferous crops are Aphidius matricariae (Haliday) and Diaeretiella rapae (M'Intosh), (Bahana and Karhioc 1986;Ohiman and Kunar 1986;Souza et al 1992;Gabrys et al 1998;Vaughn and Antolin 1998;Bijaya Devi et al 1999). Pike et al (2000) also reported the presence of Aphidius ervi (Haliday), A. matricariae, D. rapae, Ephedrus californicus (Baker) and Lysiphlebus testaceipes (Cresson) as aphid parasitoid species found on Brassica sp.…”
Section: Introductionmentioning
confidence: 99%